Limites e possibilidades das compras institucionais para o fortalecimento da agricultura familiar: estudo de caso do IFSP – campus Avaré - Watanabe, Gustavo Yoshio (2020)
The Food Acquisition Program (PAA) and the National School Feeding Program (PNAE) are public policies that have among their purposes: promoting access to food and encouraging family farming. This work has the object of study, using the case study and action research as a methodology, to analyze the shopping experience of the Federal Institute of Education, Science and Technology of São Paulo - Avaré campus together with family farming. As for the case study, it refers to the shopping experiences, comprised in the period from 2016 to 2019, when the federal autarchy started the execution of the PNAE using the Avaré campus as a pilot project. As for action research, it is supported by the fact that the researcher participated in the purchases made during this period. The data collection of the work was done through interviews with family farmers who participated, participate or never participated as beneficiaries of these policies for the IFSP - campus Avaré during the studied period. In addition to the interviews, the documentary research that brought data from notices, contracts, sales projects, among other documents, as well as the participant observation that brought contributions in the analysis of the results obtained. Finally, as regards the results, the importance of executing these purchases for family farming can be seen, demonstrated by the farmers' perceptions mainly regarding the share they represent in their incomes. However, they point out that, among the main difficulties, marketing prices are not interesting and also problems with transportation, which must be evaluated by Organs executing agencies. As for the possibilities of approximation among stakeholders, there is a need for approximation to resolve the difficulties mentioned, but positively there is an intention of involvement by the interviewees in participating in these discussions. Finally, in the context of the pandemic, it appears that there was a negative economic impact on income for farmers benefiting from these public policies due to the suspension of school deliveries, corroborating the importance and positive impact that these public policies represent for these family farmers.